Self-Evaluation Differences Among Swedish Children and Adolescents Over a 30-Year Period - Hoff, Eva V.; Daukantaitė, Daiva; Birgerstam, Pirjo (Frontiers in Psychology, 2020)
International research has found changes in how today’s young people evaluate themselves. The present Swedish research contributes with new findings by distinguishing different patterns of change in self-evaluation in two age groups. The study investigates generational and gender differences in five self-evaluation dimensions in two samples, one from 1983 (N = 3052 10-16-year-old students) and one from 2013 (N = 1303 10-18-year-old students). Three age groups were analysed. The generational comparison for primary school (ages 10-12) showed higher scores in 2013 than in 1983 for all five self-evaluation dimensions. Interactions between generation and gender were found for psychological well-being, relations to others, school competence evaluations, and the total score, demonstrating, in contrast to international research, a greater increase for girls than for boys. Noteworthy is that girls in primary school had higher scores in 2013. The generational comparison for lower secondary school (ages 13-15) demonstrated higher scores for school competence, relational self-evaluations, and a total higher score in 2013. Interactions between generation and gender were found for total, physical, and psychological well-being evaluation scores, indicating an increase for boys and a decrease for girls in 2013 compared to 1983. The gender comparison for secondary school (ages 16-18, 2013), showed gender differences for physical, psychological well-being, school competence evaluations, and for the total score to the advantage of boys. The study discusses changes in self-evaluation in relation to phenomena such as permissive child-rearing, decreased demands in school, increased self-enhancement behaviour through social media, and narrow body ideals in today’s society. The study recommends that interventions directed towards groups with low self-evaluation scores should be considered.